Caspase-12 affects chondrogenesis in mice - Veselá, Barbora; Bzdúšková, Jana; Ramešová, Alice; Holomková, Kateřina; Matalová, Eva (Annals of anatomy, 2025)
Caspase-12 is a molecule whose functions are still not well understood. Although its expression has been found in various tissues, specific roles have been described in only a few cases. These include the effect of caspase-12 on murine bone cell differentiation during craniofacial development. This work focused on the development of the limbs taking place through endochondral ossification, which precedes the formation of the cartilaginous growth plate. Caspase-12 was described here for the first time in growth plate chondrocytes during physiological development. Using pharmacological inhibition, caspase-12 was found to affect chondrogenesis. Limb-derived micromass cultures showed a significantly increased area of chondrogenic nodules after caspase-12 inhibition and there were changes in gene expression, the most significant of which was the reduction of Mmp9. These data point to potential new functions of caspase-12 in chondrogenesis.
Keywords: Animals; chondrocyty; Growth Plate; Differentiation; Growth plate; Caspase-12; Gene Expression Regulation, Developmental; Chondrogenesis; Caspase 12; buněčná diferenciace; Mice; Chondrocytes; Matrix Metalloproteinase 9; kultivované buňky; myši; kaspasa 12; Cells, Cultured; matrixová metaloproteinasa 9; chondrogeneze; inhibitory kaspas; růstová ploténka; Cell Differentiation; zvířata; vývojová regulace genové exprese; Chondrocyte; Caspase Inhibitors